1999
DOI: 10.1111/j.1600-0560.1999.tb01825.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction‐denaturing gradient gel electrophoresis (PCR/DGGE)‐based detection of clonal T‐cell receptor γ gene rearrangements in paraffin‐embedded cutaneous biopsies in cutaneous T‐cell lymphoproliferative diseases*

Abstract: Polymerase chain reaction (PCR)-based amplification of T-cell receptor (TCR)-gamma genes is a novel technique that can detect a clone of T cells comprising less than 1% of the total T cells in a lymphoid infiltrate. Besides greater sensitivity than Southern blotting, this technique can be performed with smaller quantities of lower molecular weight genomic DNA as template. We retrospectively analyzed 12 paraffin-embedded biopsies of cutaneous T-cell lymphoma (CTCL), 1 case suspicious for CTCL, 1 case of granulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Comparison of our PCR positivity rates with previously published studies showed an agreement in the findings: 50–78% clonality for patch‐stage MF (present study 62.1%); 50–100% clonality for plaque‐stage MF (present study 85.7%); 50–70% clonality for prediagnostic inflammatory dermatoses suggestive of MF (present study 50%); and 16–73% clonality for prediagnostic inflammatory dermatoses non‐specific for MF (present study 25%) 9,12,14–17 . The wide variation in sensitivity rates of published data is no doubt related to diagnostic criteria used for the histological diagnosis of MF and the sensitivity of the PCR technique.…”
Section: Discussionsupporting
confidence: 90%
“…Comparison of our PCR positivity rates with previously published studies showed an agreement in the findings: 50–78% clonality for patch‐stage MF (present study 62.1%); 50–100% clonality for plaque‐stage MF (present study 85.7%); 50–70% clonality for prediagnostic inflammatory dermatoses suggestive of MF (present study 50%); and 16–73% clonality for prediagnostic inflammatory dermatoses non‐specific for MF (present study 25%) 9,12,14–17 . The wide variation in sensitivity rates of published data is no doubt related to diagnostic criteria used for the histological diagnosis of MF and the sensitivity of the PCR technique.…”
Section: Discussionsupporting
confidence: 90%
“…The PCR/DGGE was performed using the method described previously 6,15 . Briefly, PCR for the TCR γ gene rearrangement was performed using consensus primers V γ 1–8 /J γ and V γ 9/ J γ as published previously (Table 7).…”
Section: Methodsmentioning
confidence: 99%
“…The technique has also been successfully applied to archival, paraffin‐embedded skin tissues with variable sensitivity 9, 12, 13 . We have applied the PCR/denaturing gradient gel electrophoresis (DGGE) to detect clonal TCR γ gene rearrangement on paraffin tissues successfully 15 and performed TCR gene rearrangement study in 100 cases, either on fresh‐frozen or paraffin‐embedded tissue. In this paper, we present our data to further evaluate the value of TCR gene rearrangement studies by PCR as an adjunct tool to the histological diagnosis in CTCL, and the possible difference between fresh vs. paraffin‐embedded tissues in this PCR‐based study.…”
mentioning
confidence: 99%
“…The use of PCR in the field of cutaneous T‐cell lymphoma is well established and many laboratories are offering it 9 . Molecular techniques are becoming popular in the diagnosis of Kaposi's sarcoma 10 .…”
Section: Opportunitiesmentioning
confidence: 99%
“…The use of PCR in the field of cutaneous T-cell lymphoma is well established and many laboratories are offering it. 9 Molecular techniques are becoming popular in the diagnosis of Kaposi's sarcoma. 10 In time, more and more tumors, malignant melanoma in particular, will be investigated by these techniques.…”
Section: Molecular Diagnosticsmentioning
confidence: 99%